ANALISIS LITERASI KEUANGAN TERHADAP PERILAKU PENGELOLAAN KEUANGAN, DAN SIKAP KEUANGAN SEBAGAI VARIABEL MEDIASI - Masrifah, Binti; Ruscitasari, Zulfatun; Handayani, Anik Puji (Jurnal PenKoMi : Kajian Pendidikan dan Ekonomi, 2024)
This study aims to determine the effect of Financial Literacy on Financial Management Behavior with Financial Attitudes as a Mediation Variable. The object of this study are SMEs Leather Craft Village, Yogyakarta. This research uses a Quantitative type of research with a descriptive approach. The sample used in this study was 140 SMEs in Keparakan, Yogyakarta. The data collection method used purposive sampling technique. Data processing is carried out used partial least squares and used tools Smart PLS. The results and conclusions of this study indicate that financial literacy has a direct and significant effect on financial management behavior. Financial literacy has a direct and significant effect on financial attitudes. Financial attitudes have a direct and significant effect on financial management behavior. Financial attitudes can fully mediate the effect of financial literacy on financial management behavior.